A Micro-CT Analysis of Initial and Long-Term Pores Volume and Porosity of Bioactive Endodontic Sealers - Mateusz Radwanski; Michal Leski; Adam K. Puszkarz; Jerzy Sokolowski; Louis Hardan; Rim Bourgi; Salvatore Sauro; Monika Lukomska-Szymanska (Biomedicines, 2022)
The evaluation of the porosities within the interface of root canals obturated with endodontics materials is extremely important for the long-term success of endodontic treatments. The aim of this study was to compare initial and long-term volume of pores (total, open, closed) and porosity (total, regional) of three bioactive endodontic sealers: GuttaFlow Bioseal, Total Fill BC Sealer, and BioRoot RCS. Root canals were obturated with three “bioactive” sealers using the single-cone technique. The volume of open and closed pores and porosity were calculated using a micro-computed tomography (MCT) method. The measurements were performed after 7 days (initial) and after 6 months (long-term) of incubation. Statistical significance was considered at p < 0.05. The total volume of pores remained unchanged after the 6-month storage. GuttaFlow Bioseal exhibited significantly higher long-term volume in open pores than Total Fill BC Sealer. The total porosity in all the tested sealers presented no statistically significant change after the 6-month storage, except for BioRoot RCS. The total porosity values of this latter material significantly increased after long-term incubation, especially in the apical region. In conclusion, the use of bioactive sealers with excessive tendency to create porosities both in shorth- and long-term periods of storage may compromise the long-term success of endodontic treatments.